Advances in Prevention of Foodborne Pathogens of Public Health Concern during Manufacturing - Bisha, Bledar (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
According to a report from the U.S. Centers for Disease Control and Prevention (CDC), achieving safe and healthier foods was one of the top ten achievements of public health in the 20th century. However, considerable persisting challenges currently exist in developed nations and developing economies for further assuring the safety and security of the food supplies. According to CDC estimates, as many as 3000 American adults, as an example, and based on a recent epidemiological estimate of the World Health Organization, around 420,000 individuals around the globe, lose their lives annually due to foodborne diseases. This emphasizes the need for innovative and emerging interventions, for further prevention or mitigation of the risk of foodborne microbial pathogens during food processing and manufacturing. The current publication discusses recent advancements and progress in the elimination and decontamination of microbial pathogens during various stages of manufacturing and production. Special emphasis is placed on hurdle validation studies, investigating decontamination of non-typhoidal Salmonella enterica serovars, various serogroups of Shiga toxin-producing Escherichia coli, public health-significant serotypes of Listeria monocytogenes, and pathogenic species of Cronobacter.